2013
DOI: 10.1155/2013/750128
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Theory‐Driven Nutritional Education Program in Improving Calcium Intake among Older Mauritian Adults

Abstract: Background. Low calcium intake, a risk factor of osteoporosis and subsequent fractures, has been previously reported among post-menopausal women in Mauritius. Objective. To assess the effectiveness of a theory-based educational intervention in improving the calcium intake, self-efficacy, and knowledge of older Mauritians. Methodology. The study was conducted as a pre- and post-test design which was evaluated through a baseline, immediate postintervention, and 2-month follow-up assessments. Participants were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Also, older respondents have higher nutrition knowledge compared to their younger counterparts as they have been exposed to more nutritional information [19]. In their study, Bhurosy and Jeewon [20] also reported higher knowledge scores in older adults after a nutrition education program. In this study, presence of an elderly person affected nutrition knowledge score whereas having children had no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Also, older respondents have higher nutrition knowledge compared to their younger counterparts as they have been exposed to more nutritional information [19]. In their study, Bhurosy and Jeewon [20] also reported higher knowledge scores in older adults after a nutrition education program. In this study, presence of an elderly person affected nutrition knowledge score whereas having children had no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Hazavehei et al also reported an increase in walking and calcium intake in the intervention group after the education ( 12 ). In a study by Bhurosy et al using the HBM on 189 people aged ≥ 40 years could significantly increase the calcium intake of the study participants ( 25 ). Similar findings were also reported by Jung et al who trained young females through targeted messages ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…50,51,[76][77][78] Nurses can apply these intervention strategies in practice to promote behavior changes. 58,[79][80][81] Nurses can be part of the efforts to participants in research studies. Information developed for the public and guidelines for assessing and treating patients with osteoporosis are available from many agencies and organizations, such as the National Institutes of Health and the National Osteoporosis Foundation, [1][2][3]8 and can be used effectively to introduce the topic to patients and to follow up accordingly.…”
Section: Strengthening Patients' Health Beliefs and Promoting Behaviomentioning
confidence: 99%